HIV Interactions with Dendritic Cells Infection and Immunity - Wu, Li.; Schwartz, Olivier; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Given rapid research progress and advance of the techniques in studying HIV interactions with host cells and factors, there is a critical need for a book on HIV interactions with DCs. The proposed book will aim for a broad readership to facilitate HIV/AIDS research and provide a practical tool for HIV researchers to continuously address novel questions. Specifically, the editors will summarize the literature in this field and provide critical analysis and future directions. International researchers will be invited as contributors of the book, highlighting authors who have contributed significantly to the field from different angles and aspects of virology, cell biology and immunology, etc.
Preface -- Immunobiology of dendritic cells and the influence of HIV infection -- Antiviral immune responses by human Langerhans cells and dendritic cells in HIV-1 infection -- Plasmacytoid dendritic cells in HIV infection -- Cellular and viral mechanisms of HIV transmission by dendritic cells -- Role of glycosphingolipid in dendritic cell-mediated HIV-1 trans-infection -- Simian immunodeficiency virus interactions with macaque dendritic cells -- Interactions between HIV-1 and innate immunity in dendritic cells -- HIV impairment of immune responses in dendritic cells -- HIV-derived vectors for gene therapy targeting dendritic cells -- Targeting dendritic cells for improved HIV-1 vaccines -- Index.
Keywords: Medicine; Immunology; Microbiology; Medical virology; Biomedicine; Virology; Immunology; Medical Microbiology; Medicine/Public Health, general